Immune-Related Adverse Events and Corticosteroid Use for Cancer-Related Symptoms Are Associated With Efficacy in Patients With Non-small Cell Lung Cancer Receiving Anti-PD-(L)1 Blockade Agents - Riudavets, Mariona; Mosquera, Joaquin; Garcia-Campelo, Rosario; Serra, Jorgina; Anguera, Georgia; Gallardo, Pablo; Sullivan, Ivana; Barba, Andrés; del Carpio, Luís; Barnadas, Agustí; Gich, Ignasi; Majem, Margarita (Frontiers in Oncology, 2020)
Background Immune-related adverse events (irAEs) have been associated with improved efficacy in advanced non-small cell lung cancer (NSCLC) patients receiving anti-PD-(L)1 blockade agents, while the concurrent use of corticosteroids seems to worsen it. We evaluated outcomes in advanced NSCLC patients treated with anti-PD-(L)1 blockade agents in relation to the presence of irAEs and the reasons for using corticosteroids: whether for palliative cancer-related reasons or for the management of irAEs. Methods Clinical outcomes in advanced NSCLC patients treated with anti-PD-(L)1 blockade agents were calculated with regard to the presence of irAEs and the use of corticosteroids. A landmark analysis was performed to avoid immortal time bias due to the time-dependent nature of irAEs. Results Out of a total of 267 patients, the 56.9% of patients who experienced irAEs had significantly improved outcomes. In the landmark analysis, median progression-free survival was 12.4 months for patients with irAEs vs 4.1 months for patients without irAEs (p < 0.001), while median overall survival was 28.2 vs 12.5 months, respectively (p < 0.001). Likewise, objective response and disease control rates were significantly higher in patients experiencing irAEs: 48.6% vs 22.8% and 77.1% vs 39.6% (p <0.001), respectively. Median OS was significantly shorter for patients receiving ≥ 10mg of prednisone equivalent daily for cancer-related symptoms than for the rest of patients (<10 mg prednisone equivalent daily or for management of irAEs): 6 vs 15.9 months (p <0.001). Conclusions IrAEs were associated with improved efficacy in advanced NSCLC patients when a landmark analysis was applied. Patients receiving corticosteroids had significantly poorer outcomes when they were used for cancer-related symptoms.